ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT DALAM PENEMUAN KASUS PNEUMONIA BALITA DI PUSKESMAS KOTA PEKALONGAN - Anonim, Tri; Inayah, Maslahatul; Hartono, Mardi (JURNAL LITBANG KOTA PEKALONGAN, 2015)
THE COVERAGE OF TODDLER PNEUMONIA IN PEKALONGAN CITY ON 2009 IS 10,37% WHILE ON 2010 DECREASE TO 8,49%, THIS FIGURE IS STILL FAR UNDER THE TARGET, COMPARED WITH THE SPM (MINIMUM SERVICE STANDARDS) TARGET ON 2010 IS 100%. THE DECREASE OF THIS COVERAGE SHOWS ABOUT THE PERFORMANCE OF NURSES IN THE DISCOVERY OF TODDLER PNEUMONIA IS DISSATISFACTORY. THE AIM OF THIS STUDY IS TO KNOW WHICH FACTORS THAT DETERMINE THE PERCEPTION OF ABILITIES AND SKILLS, RESOURCES, PERCEPTION OF LEADERSHIP, PERCEPTIONS OF SUPERVISION, AND ATTITUDES WHICH RELATED TO THE PERFORMANCE OF NURSES IN THE DISCOVERY OF TODDLER PNEUMONIA IN HEALTH CENTER OF PEKALONGAN CITY. THIS STUDY USES CROSS SECTIONAL DESIGN WITH THE SAMPLE OF 30 RESPONDENTS CONSISTED OF ALL THE NURSES WHO HANDLE THE ADMINISTRATION OF TODDLER PNEUMONIA IN 12 HEALTH CENTERS IN PEKALONGAN CITY. METHODS OF DATA COLLECTION IS USING STRUCTURE QUESTIONNAIRES TO THE NURSES. DATA WERE ANALYZED QUANTITATIVELY USING STATISTICAL TEST PEARSON PRODUCT MOMENT CORRELATION COEFFICIENT. THE RESULT OF THIS STUDY SHOWS THAT THE RESPONDENTS HAVE SATISFACTORY PERCEPTION OF ABILITIES AND SKILLS 70%, SATISFACTORY PERCEPTION OF RESOURCES 63,3%, THE DISSATISFACTORY PERCEPTION TOWARDS THE LEADERSHIP OF 56,7%, DISSATISFACTORY PERCEPTION TOWARDS SUPERVISION ACTIVITIES, THE SATISFACTORY ATTITUDE OF NURSES 53,3%, AND MOST OF THE NURSES’ PERFORMANCE IN THE CASES DISCOVERY OF TODDLER PNEUMONIA WITH 56,7% SATISFACTORY CATEGORY. BIVARIATELY SHOWS THAT THE INDEPENDENT VARIABLES WHICH ARE NOT RELATED TO THE NURSES’ PERFORMANCE IN THE CASES DISCOVERY OF TODDLER PNEUMONIA IS ABILITIES AND SKILLS VARIABLES, RESOURCES PERCEPTION (P>0.05), WHILE THE INDEPENDENT VARIABLE WHICH IS RELATE TO THE DEPENDENT VARIABLE IS THE LEADERSHIP PERCEPTION (P=0,000